Comparison of clinical effectiveness of diverting seton and cutting seton for supra-sphincteric fistula - Lin Wenhua; Lü Shirong (结直肠肛门外科)
[Objectives] To compare the clinical effectiveness of diverting seton and cutting seton for supra-sphincteric fistula. [Methods] A retrospective study was performed on 40 patients with supra-sphincteric fistula treated at the Department of Anorectal Surgery, Anxi County Hospital, between June 2017 and June 2022. Based on the surgical procedure, patients were divided into the observation group (receiving diverting seton, n=20) and the control group (receiving cutting seton, n=20). Clinical effectiveness (including overall treatment effectiveness and recurrence), postoperative recovery, postoperative pain level, and postoperative anal function were recorded and compared between the two groups. [Results] During the 6-24 month follow-up, there were 16 cured cases, no remarkably effective cases, 3 effective cases, and 1 recurrence in the observation group. In the control group, there were 15 cured cases, no remarkably effective cases, 3 effective cases, and 2 recurrences. Postoperative hospitalization time and time to wound healing were shorter, and pain scores according to the Visual Analogue Scale at 7 and 14 days after surgery were lower in the observation group (P<0.05). The Wexner anal incontinence score was lower in the observation group at 3 months after surgery (P<0.05), and the control function of formed stool was normal in both groups. [Conclusion] In conclusion, the clinical effectiveness of diverting seton and cutting seton for supra-sphincteric fistula were comparable. Patients who received diverting seton treatment experienced less impact on postoperative anal function and achieved satisfactory recovery.